Development of automotive packaging by applying the QFD method - Rubert, Clauber Koenigkam; Carvalho, Cleginaldo Pereira de [UNESP]; Almeida, Maria da Gloria Diniz de; Barros, Jose Glenio Medeiros de; Sampaio, Nilo Antonio de Souza (Sindicato Secretarias Estado Sao Paulo, 2023)
The main operational functions of packaging are: containment, protection/conservation, promotion of the product and/or linking a message, i.e. packaging is almost a part of product marketing. In the automotive industry, the packaging developed serves as a means of packaging and transport ensuring the integrity of the product within the supply chain, at the best cost and within the established deadlines. This paper discusses how Quality Function Deployment (QFD) proves to be an effective methodology for ensuring success in automotive packaging development. The study is delimited to the development of packaging at a vehicle manufacturer in the southern region of the state of Rio de Janeiro. It is expected that the House of Quality, the first stage of the QFD method, presented in this article and used by the packaging development sector, can attract more teams and organizations to adopt QFD in the development of packaging, identifying, and meeting the needs of the company's internal customers and guiding external suppliers in the development of this packaging, aiming for better quality and lower cost packaging.
Keywords: Packaging Development; Quality Function Deployment (QFD); House of Quality (HoQ); Simultaneous Engineering